2022
DOI: 10.1155/2022/5904332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Predictors of Mortality in Elderly Patients Hospitalized with COVID-19 in Bangladesh: A Multicenter, Retrospective Study

Abstract: Purpose. Elderly patients are at high risk of fatality from COVID-19. The present work aims to describe the clinical characteristics of elderly inpatients with COVID-19 and identify the predictors of in-hospital mortality at admission. Materials and Methods. In this retrospective, multicenter cohort study, we included elderly COVID-19 inpatients (n = 245) from four hospitals in Sylhet, Bangladesh, who had been discharged between October 2020 and February 2021. Demographic, clinical, and laboratory data were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…In the present study, age, IGs, LDH, ferritin, chest X-ray score and the absence of full vaccination, cough and fatigue were significantly and independently associated with the in-hospital mortality of this older population. -------------------------- The majority of these findings are consistent with those of previous studies of the in-hospital mortality of elderly patients with COVID-19 (14,16,(24)(25)(26)(27). Among studies in the general population, age has been reported as an independent predictor of mortality within 1 year after COVID-19 (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, age, IGs, LDH, ferritin, chest X-ray score and the absence of full vaccination, cough and fatigue were significantly and independently associated with the in-hospital mortality of this older population. -------------------------- The majority of these findings are consistent with those of previous studies of the in-hospital mortality of elderly patients with COVID-19 (14,16,(24)(25)(26)(27). Among studies in the general population, age has been reported as an independent predictor of mortality within 1 year after COVID-19 (28,29).…”
Section: Discussionsupporting
confidence: 89%